Repeatability of the 6-min walk test in non-cystic fibrosis bronchiectasis - Rovedder, Paula Maria Eidt (Sci Rep, 2020)
Non-cystic fibrosis bronchiectasis (NCFB) is a chronic lung disease characterized by progressive and irreversible changes of the bronchial tree. The evaluation of exercise capacity is essential to manage this disease. This study aims to determine the within-subject repeatability of two Six Minute Walk Test (6MWT) in adults with NCFB. NCFB. This cross-sectional observational study included 66 NCFB subjects above 18 years-old (mean of 55 ± 17 years old, 68% women). 73% of the participants presented moderate to severe clinical condition classified by Bronchiectasis Severity Index. It showed that these participants walked 16.6 m less (95%CI 3.8 to 29.4; p < 0.01) in the second 6MWT when compared to the first test, with a within-subject coefficient variation of 9.4% (95%CI 7.2–11.2%) and an intra-test reliability with a high intraclass correlation coefficient of 0.88 (95%CI 0.80–0.93). Bland–Altman plot showed an agreement regarding test repeatability, besides presented a large limit of agreement (− 85 to 116 m). Respiratory rate and systolic blood pressure were significantly higher before starting the second test. In conclusion, 6MWT seems to be reproducible in NCFB subjects and vital sign verification should be attentively checked to assess if the patient is fully recovered to perform a second test, as well as the disease severity score. Other studies on this matter should be conducted with a larger number of participants to confirm the findings of the present study.